Dejavniki, ki se povezujejo s socialno sprejetostjo v različnih obdobjih šolanja - Košir, Katja (Psihološka obzorja (Ljubljana), 2007)
In the eighties and nineties of the previous century researchers started to investigate the characteristics of the pupils from different sociometric groups. However, such studies were seldom performed with adolescents and also did not include different age groups of pupils. The purpose of the present research was to explore the factors of pupils' social acceptance in three different periods of schooling - in late childhood, middle adolescence, and late adolescence. Pupils (N=1159) from 49 classrooms of elementary and secondary schools participated in the study. Academic and nonacademic characteristics were included as potential factors of social acceptance. To assess different factors validly, three various sources of information were used: peer report, teachers' report, and self-report. The characteristics of pupils that proved to be the factors of social acceptance in all periods of schooling are: peer perceived kindness, prosocial behaviour, impulsiveness, audacity, popularity, and the number of friendships. Academic behavious was a significant factor of social acceptance in four-grade pupils and, to a smaller extent, also in older pupils. In all three periods of schooling the differences between pupils of different sociometric groups were the weakest for the measures of self-report.
Keywords: socialna sprejetost; šolanje; učenci; psihologija; psychology; starostne razlike